Unveiling dark patterns in social networks: online choice architecture and the relevance of competition - Mattiuzzo, Marcela (2023)
The goal of this thesis is to carry out an assessment of dark patterns in social networks, and to analyze whether the existing legal framework in some jurisdictions notably, Brazil, the European Union, and the United States of America allows for such practices to be deemed unlawful when they are harmful to consumers and markets. To do so, the work is divided into four main parts. The first chapter provides an overview of dark patterns, by looking at existing studies on the topic, proposes a working definition for the concept, and assesses to what extent the concept is applicable to social networks. The second chapter is focused on a case study of one social network, TikTok, and aims at concretely verifying if one can see instances in which the use of online choice architecture can be perceived as amounting to dark patterns, and to what extent the working definition is helpful towards that end. The third chapter moves on to discuss in more detail what the impacts of dark patterns can be, for individual users and for markets. It shows that though repercussions on an individual level are relevant, the market- wide consequences of the deployment of dark patterns can be equally pertinent. The fourth chapter zooms in on the legal and policy debate. It first intends to provide an overview of existing legislation in the aforementioned jurisdictions that can be deployed to tackle dark patterns, and how enforcement already has or potentially could be carried out. It does so by focusing on the rules applicable to the digital acquis, more precisely on norms pertaining to consumer law, data protection/privacy, and competition/antitrust. Lastly, after concluding that the legislation currently in place does provide options for authorities to address issues running from dark patterns, it engages in a debate about the framework needed for more broadly addressing issues brought about by online choice architecture.